Editorial (The Reasoner, 2025)
The Editorial Team welcomes readerst to The Reasoner new home.
Keywords: Book reviews; News; Uncertain Reasoning; History of Logic and Reasoning; Medical Reasoning and Medical Methodology; Reasoning and AI; Causal Reasoning